Effects of a body-weight supporting kite on sprint running kinematics in well-trained sprinters - Kratky, S.; Buchecker, M.; Pfusterschmied, J.; Szekely, C.; Müller, E. (The Journal of Strength and Conditioning Research, 2016)
Data of elite sprinters indicate that faster athletes realize shorter ground contact times compared with slower individuals. Furthermore, the importance of the so-called "front side mechanics" for elite sprint performance is frequently emphasized by researchers and coaches. Recently, it was demonstrated that using a body-weight supporting kite during full-effort sprints in highly trained sprinters leads to a reduction in ground contact time. The aim of this study was to investigate possible negative effects of this body-weight supporting device on sprint running kinematics, which was not clarified in previous studies. Eleven well-trained Austrian sprinters performed flying 20-m sprints under 2 conditions: (a) free sprint (FS); and (b) body-weight supported sprint (BWS). Sprint cycle characteristics were recorded during the high-speed phase by a 16 camera 3D-system (Vicon), an optical acquisition system (Optojump-next), and a high-speed camera. Paired sample t-tests and Cohen's d effect size were used to determine differences between sprinting conditions. Compared with FS, BWS caused a decrease in ground contact time by 5.6% and an increase in air time by 5.5% (both p < 0.001), whereas stride length and rate remained unchanged. Furthermore, a reduced hip joint extension at and after take-off, an increased maximal hip joint flexion (i.e., high knee position), and a smaller horizontal distance of the touchdown to the center of gravity could be observed (all p < 0.01). These results indicate no negative effects on front side mechanics during BWS and that sprinting with a body-weight supporting kite seems to be a highly specific method to reduce ground contact time in well-trained sprinters.